Single-inductor dual-output DC-DC buck converter with time-multiplexing technique for integrated battery management system - Do, Tuan Hung (2014)
In this project, a dual-output buck DC-DC converter is using 0.18um CMOS technology. Time-multiplexing technique will be implemented, which requires only one off-chip inductor. The input supply voltage is from a 2.7-3.3V battery, while the two outputs are specified at 1.8V for analog circuits and 1V for digital circuit applications. The circuit needs to achieve high accuracy, low complexity, small area and low power consumption. Special circuitries will be used in the implementation of the circuit, including Zero-Crossing Detection of Inductor Voltage, Time Multiplexing Control.